PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 005 SUNGAI SEGAJAH KECAMATAN KUBU KABUPATEN ROKAN HILIR - Sri Rahayu; Lazim N Lazim N; Zulkifli Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrak: The rescearch is cause is the low science,s studies students learning outcomes with average grade 57,87. While the udue of minimum criteria of completenes is 65 this researches is classroom action research (CAR). That suppose to incriasing of the science,s studies students learning outcomes of fourth grade of elementery school 005 Sungai Segajah Kubu in Rokan Hilir district. The formula of the problem is does the aplication of cooperative learning model type Think Pair Share (TPS) can inprove the science,s studies studen learning outcomes of fourth grade SDN 005 Sungai Segajah Kubu in Rokan Hilir District. . Before dairy CAR the students good average grade 57,87. Ard after CAR the average grade in create is 65,83% whereas on the scord cycle the average grade increase is 70. So the improvement of students learning out comes from the bassed score to cycle I increase about 13,75% whereas from based score to cycle II increase about 20,96%. The activity of the student in first cycle with an average grade 58,33% and the scord cycle is about 70,83%. The activity of the teacher on the first cycle with an average grade 54,16% and the secord cycle is about 66,66%. The result of this research is the application of cooperative learning model type Think Pair Share (TPS) can increase the science,s studies students learning outcomes at fourth brade of elementary school 005 Sungai Segajah Kecamatan Kubu in Rokan Hilir District.Key Word : Kooperative type Think Pair Share (TPS) The science,s student achievement